Analysis of Postal Agent Performance in Sidoarjo Seen from External and Internal Factors - Triastuti, Wahyu Ria (Universitas Syiah Kuala, 2024)
The momentum of COVID-19 should be an opportunity for courier business owners because many people focus on their activities at home and rely on courier services to shop. Two big players such as JNE and JnT have shown an increase in transaction volume in 2020 and 2021. On the other hand, Pos Indonesia has experienced a 15% decrease in profit from usual. This phenomenon is also reflected in the scale of Postal Agents, one of the official partners of Pos Indonesia. Referring to data from the Central Post Office in Sidoarjo , the income of all Postal Agents in Sidoarjo decreased by around 15% during the pandemic, starting in 2020 Rp. 11.3 billion to Rp. 9.6 billion in 2021. This research was conducted to investigate the influence of aspects of external and internal factors on the performance of Postal Agents. All research data comes from questionnaires filled out by 30 respondents who are managers of Postal Agents in Sidoarjo. Then the data was analyzed using the SEM-PLS (Structural Equation Modeling Partial Least Square) method. The results showed that internal factors had a positive influence on the performance of Postal Agents with a T-statistic of 3.115 and a P-value of 0.002 (0.05). From these internal factors, it is known that finance and service products are the most influential aspects. Meanwhile, external factors did not have a positive influence on the performance of Postal Agents with a T-statistic of 0.123 and a P-value of 0.902 ( 0.05).